2021
DOI: 10.1021/acs.jafc.0c06487
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Porphyrin Metal–Organic Framework with Desirable Photodynamic Antimicrobial Activity for Sustainable Plant Disease Management

Abstract: Considering the severity of plant pathogen resistance toward commonly used agricultural microbicides, as well as the potential threats of agrichemicals to the eco-environment, there is a pressing need for antimicrobial approaches that are capable of inactivating pathogens efficiently without the risk of inducing resistances and harm. In this work, a porphyrin metal–organic framework (MOF) nanocomposite was constructed by incorporating 5,10,15,20-tetrakis­(1-methyl-4-pyridinio)­porphyrin tetra­(p-toluenesulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“… Pseudomonas putida; Pseudomonas elongata; Pseudomonas geniculata; Pseudomonas pavonacea Pseudomonas putida Tomato Plant growth, yield Inoculum with different carbon sources Hexa-chlorocyclohexane-degrading consortium Mineral uptake enhancement by 12–19% with respect to control Shen et al. (2012) , Tang et al. (2021 b) Cherry trees Fruit set, plant vegetative growth Maize Grain yield 5.…”
Section: Pseudomonas Mediated Establishment Of Rhizospheric Competencymentioning
confidence: 99%
“… Pseudomonas putida; Pseudomonas elongata; Pseudomonas geniculata; Pseudomonas pavonacea Pseudomonas putida Tomato Plant growth, yield Inoculum with different carbon sources Hexa-chlorocyclohexane-degrading consortium Mineral uptake enhancement by 12–19% with respect to control Shen et al. (2012) , Tang et al. (2021 b) Cherry trees Fruit set, plant vegetative growth Maize Grain yield 5.…”
Section: Pseudomonas Mediated Establishment Of Rhizospheric Competencymentioning
confidence: 99%
“…As an emerging class of porous materials, metal–organic frameworks (MOFs) with unique properties have been applied in many fields. At present, studies have been conducted on the use of MOFs in pesticides such as pesticide sensing [ 23 ], delivery [ 24 , 25 , 26 ], adsorption, and photodegradation [ 27 ]. In our previous work, we also prepared pesticide-loaded Fe-MIL-100 [ 28 ] and NH 2 -Fe-MIL-101 [ 29 ] and studied the controlled release profiles of AZOX and Dini, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops showed a similar level of Pseudomonas abundance, however inorganic fertilizer had higher relative abundance (57.1%) than the poultry litter (55%) treatment (Figure S1b). It has been reported that the genus Pseudomonas promotes phosphate solubilization, nitrogen fixation, induced systemic resistance, and siderophore production, thus favoring plant growth and phytopathogen control, hence acting as a bioinoculant [70][71][72]. The genus, Rhodoplanes depicted higher abundance in cereal rye and native vegetation (4.9%) compared to wheat and vetch (Figure S1a).…”
Section: Impact Of Management Practices On the Bacterial Community Ab...mentioning
confidence: 93%